Peran kepemimpinan mengayomi terhadap keterlibatan kerja: Apakah jenis kelamin tertentu lebih diuntungkan? - Saraswati, Amatya; Rocky, Rocky (Konsorsium Psikologi Ilmiah Nusantara, 2024)
Work engagement is a crucial factor in employee performance. Leadership style is one of the factors that determine work engagement. Leaders, thus, need to adapt their leadership style to the preference of their employees. This research offers mengayomi (nurturing) leadership as a suitable style in Indonesian society. Specifically, the present study seeks to understand the relationship between mengayomi leadership style with work engagement moderated by gender. This research uses quantitative methods. This study involved 164 employees in Jakarta as respondents who were selected using convenience sampling. Data analysis was performed using regression technique. The results showed that mengayomi (nurturing) leadership significantly improves work engagement. Furthermore, the effect was observed to be stronger among male participants. This findings suggest that organizations should promote and train leaders in mengayomi leadership to enhance employee engagement, and consider gender differences to tailor leadership approaches more effectively.